Análisis de la avifauna en los cantones: La Maná, Pangua, Latacunga, Pujilí, Sigchos y Salcedo de la provincia de Cotopaxi. - Bolaños Tapia, Janina Nataly (2018)
The Province of Cotopaxi is identified by being composed of seven cantons each with unique and different characteristics such as climates, geographical location, it is one of the few provinces where the mountains and the coast are located a few kilometers away, for this reason it has a wealth considerable in flora and fauna, focusing on avifauna species was determined through the sources consulted that the information was not updated approximately three years ago, which is why this research has been developed; obtaining as result an analysis that focused on the validation of the data obtained previous bibliographical consultation in previous investigations that allowed to update a database of the bird species of the six cantons of study that are Latacunga, Salcedo, Pujilí, Sigchos and Pangua , perform a comparative analysis determining the most representative species and the abundance of each sector obtaining a total of 1848 individuals distributed indistinctly: Latacunga (679) being this the site that has the highest index, followed by Pujilí with (403), Sigchos with ( 382), Pangua (170), Salcedo (136) and La Maná with a total (80) being the sector with the lowest number of registered specimens, 172 types of different species, in a total of 42 families distributed in 21 orders. It was determined in turn in the comparative analysis that the Passeriform Order with a total of 1121 is the most abundant followed by the Apodiformes with 217 individuals; using Sorensen's similarity index, it was identified that there is a great variety of species that characterize each of the study areas. These data were obtained thanks to the systematization of the information using Tic's tools such as Microsoft Excel for the generation of the species tables, interpretation and calculation of the new information obtained through graphs and dynamic tables, The Current Version EstimateS 9.1.0 program. for the calculation of the Sorensen index, ArcGIS for the layout of the Distribution Map and Adobe Illustrator CC for the layout of the Bird Guide. For the elaboration of the guide the photographs were taken from the internet to have a clearer and faster identification of each of these species when using our guide in the field since the facilitated ones were not of good quality, the design of the It is the author's own authorship and was based on examples of reference guides taken, such as the Peterson Bird Guide and the Bird Book of Ecuador. Facilitating an updated avifaunistic dissemination instrument for professionals, students and lovers of tourism and bird watching of the Province and the Country.